Take change of your finances - Heatter, Justin W. (Scribner, 1984)
This no-bull, bottom-line guide from "The Reformed Broker" Josh Brown and Yahoo Finance's Jeff Macke will help you cut through the cacophony and make the most of today's media news. It's an eye-opening crash course in separating financial facts from fiction—featuring interviews with some of the world’s most influential investors